Penerapan Metode Literasi dalam Meningkatkan Mutu Pembelajaran SKI di MA Darul Faizin Catak Gayam Jombang - Sari, Dila Puspita; Umam, Khoirul (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited research on the application of literacy methods in the teaching of Islamic Cultural History (Sejarah Kebudayaan Islam or SKI), despite its significant potential to enhance the quality of instruction at the madrasah level. The aim of this research is to explore the application of literacy methods in improving the quality of SKI instruction at MA Darul Faizin Catak Gayam Jombang. A qualitative approach with a case study design was used, with a single madrasah selected as the research subject through purposive sampling. Data were collected through observation, interviews with teachers and students, and analysis of instructional documents, and were analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings indicate that the application of literacy methods has a positive impact on improving the quality of SKI learning. Institutional support, teacher creativity in developing text-based teaching materials, and student enthusiasm for reading activities were key factors supporting the success of this implementation. These findings reinforce the theory that literacy-based approaches can enhance comprehension, critical thinking skills, and student learning interest. The main conclusion of this study is the importance of integrating literacy methods into SKI instruction to promote a reading culture and strengthen students’ reasoning abilities. The implications of this study include theoretical contributions to the development of literacy-based instructional models and practical recommendations for teachers to design systematic and contextual literacy-based learning strategies. This research also opens opportunities for further studies on the impact of literacy methods on learning outcomes in other subjects.